Whole breast irradiation vs. APBI using multicatheter brachytherapy in early breast cancer – simulation of treatment costs based on phase 3 trial data - Harat, Aleksandra; Harat, Maciej; Makarewicz, Roman (Journal of Contemporary Brachytherapy, 2016)
Purpose: A recent large phase 3 trial demonstrated that the efficacy of accelerated partial-breast irradiation (APBI) in the treatment of early breast cancer is non-inferior to that of whole breast irradiation (WBI) commonly used in this indication. The aim of this study was to compare the costs of treatment with APBI and WBI in a population of patients after conserving surgery for early breast cancer, and to verify if the use of APBI can result in direct savings of a public payer. Material and methods : The hereby presented cost analysis was based on the results of GEC-ESTRO trial. Expenditures for identified cost centers were estimated on the basis of reimbursement data for the public payer. After determining the average cost of early breast cancer treatment with APBI and WBI over a 5-year period, the variance in this parameter resulting from fluctuations in the price per single procedure was examined on univariate sensitivity analysis. Then, incremental cost-effectiveness ratio (ICER) was calculated to verify the cost against clinical outcome. Finally, a simulation of public payer’s expenditures for the treatment of early breast cancer with APBI and WBI in 2013 and 2025 has been conducted. Results: The average cost of treatment with APBI is lower than for WBI, even assuming a potential increase in the unit price of the former procedure. There was no additional health benefit of WBI and the calculation of cost-effectiveness was based on the absolute difference in overall local control rate. However, this difference (0.92% vs. 1.44%) was fairly minimal and was not identified as statistically significant during 5 years. Conclusions : The use of APBI as an alternative to WBI in the treatment of early breast cancer would substantially reduce healthcare expenditures in both 2013 and 2025, even assuming an increase in the price per single APBI procedure.